Developing a Pipeline for the Community-Based Primary Care Workforce and Its Leadership. (September 2015) - Shtasel, Derri; Hobbs-Knutson, Katherine; Tolpin, Harriet; Weinstein, Debra; Gottlieb, Gary L.
<x xml:space="preserve">Abstract</x> Problem Community health centers (CHCs) face challenges recruiting and retaining primary care clinicians. Providing advanced training that enhances clinical skills within a public health framework, teaches leadership, protects time for scholarly activities, and focuses on the social mission may be a successful career development strategy. Approach In July 2012, the Kraft Center for Community Health Leadership developed and implemented two 2-year programs to develop physician and nursing leaders with blended academic–community career paths and identities. The fellowship program for physicians and the practitioner program for early-career physicians and advanced practice nurses include mentored practice in a CHC; monthly learning days; completion of a community-based research project; and, for fellows, matriculation in an MPH program and engagement in a bimonthly leadership seminar. Outcomes The first classes of 5 fellows and 14 practitioners graduated in June 2014. All 5 fellowship graduates were offered full-time positions at the CHCs where they practiced, and 2 have accepted leadership positions at their CHCs. All 14 practitioner graduates remain in community health, 5 have accepted leadership positions, and 2 have obtained grants to support ongoing projects. Next Steps The authors are tracking graduates' career paths and the programs' impact on CHCs while modifying the programs on the basis of feedback; identifying elements of the programs that may be amenable to more cost-effective delivery; and exploring the potential for federal funding to support expansion of the practitioner program, and for the practitioner program to increase the return on investment provided by the National Health Service Corps.